PELAKSANAAN SUPERVISI AKADEMIK DIMASA PANDEMI COVID-19 PADA MADRASAH BINAAN DI KECAMATAN SIRIMAU KOTA AMBON - Mokh Fatoni (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2022)
After the outbreak of the Covid-19 Pandemic in Indonesia in mid-March 2020, the central and regional governments quickly set an order in terms of education that is temporarily eliminating direct face-to-face learning and replaced with online learning, both at elementary and secondary school levels, and at the level of College. This order aims to break the chain of spread of this epidemic. Provisions for distance learning through online school methods that are suddenly applied certainly bring various obstacles. The writing of this article aims to identify the implementation of the distance learning process through online school methods. The author uses descriptive qualitative methods to describe and explain comprehensively and specifically related to events or phenomena that occur at this time, so that the goals of online schools can be achieved optimally. The results of the discussion found that in its implementation, the concept of online schooling brought constraints and significant impacts for both children as students and teachers as teaching staff. Lack of adequate supporting facilities and limited understanding of technology and internet network access are the main obstacles felt by both parties. In addition, it was also found that the role of supervision and attention of parents to children in the online learning process is very important for the realization of optimal learning outcomes.